2021
DOI: 10.3390/ijerph18084212
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Oral Health in Anorexia Nervosa: Comparison of a Self-Report Questionnaire and a Face-to-Face Interview

Abstract: Behavioral, nutritional, and local risk factors for oral health are frequent in people with anorexia nervosa. However no self-report questionnaire is available for screening in clinical practice or for research purposes. The objective of this study was to design a questionnaire to identify risk factors and symptoms of oral diseases and to test its reliability as a self-report form among people with anorexia nervosa. A 26-item questionnaire was designed based on a sound literature review performed by a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Nevertheless, the AN subgroups with purging episodes had worse dental erosion results [126]. Moreover, recent studies reported that 47.3% of AN patients declared suffering from bleeding gums after tooth brushing as the most prevalent oral health symptom, 37.5% of patients also regularly complained of tooth hypersensitivity [132].…”
Section: Dental Health In Anorexiamentioning
confidence: 99%
“…Nevertheless, the AN subgroups with purging episodes had worse dental erosion results [126]. Moreover, recent studies reported that 47.3% of AN patients declared suffering from bleeding gums after tooth brushing as the most prevalent oral health symptom, 37.5% of patients also regularly complained of tooth hypersensitivity [132].…”
Section: Dental Health In Anorexiamentioning
confidence: 99%
“…This indicates a partial adaptation of the organism to severe conditions during malnutrition Paszynska [ 49 ] Poland To establish the oral status regarding caries incidence, tooth wear, gingival inflammation, and oral hygiene levels among severely ill adolescent inpatients diagnosed with AN Case–control cross‐sectional survey, clinical examination of dental wear N = 220 AN Study findings indicate impaired dental and gingival conditions in young people with anorexia. Considering AN’s potential role in oral health, it is essential to monitor dental treatment needs and oral hygiene levels in their present status to prevent forward complications in the future Rangé [ 51 ] France To design a questionnaire to identify risk factors and symptoms of oral diseases and to test its reliability as a self-report form among people with AN Self-report questionnaire, face-to-face repeat questionnaire administered by dentist N = 69 AN The study authors developed and tested a questionnaire that identifies risk factors and symptoms of oral diseases in anorexia nervosa. The 26-item form of the questionnaire (long version) is moderately reliable as a self-reported form.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the studies used case–control designs to compare oral health findings between people with/at risk for eating disorders and healthy controls/those not at risk. An additional six studies described oral health effects and risk behaviors in patients with diagnosed eating disorders [ 41 , 44 , 47 , 51 , 53 , 54 ]. Findings from these studies indicate negative effects of eating disorders on oral health including tooth erosion, increased size of salivary glands, and gingival recessions at higher rates than control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation